2017
DOI: 10.1186/s41240-017-0075-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water physico-chemical parameters on tilapia (Oreochromis niloticus) growth in earthen ponds in Teso North Sub-County, Busia County

Abstract: Small-scale fish farmers in developing countries are faced with challenges owing to their limited information on aquaculture management. Nile tilapia farmers in Teso North Sub-County recorded lower yields than expected in 2009 despite having been provided with required inputs. Water quality was suspected to be the key factor responsible for the low yields. This study sought to assess the effects of earthen pond water physico-chemical parameters on the growth of Nile tilapia in six earthen fish ponds under semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
88
6
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 9 publications
21
88
6
10
Order By: Relevance
“…The average values of water quality parameters such as temperature, transparency, pH, dissolved oxygen, nitrite, nitrate, and ammonia monitored throughout the trials were considered as suitable for the survival, normal growth, as well as good general physiology of O. niloticus. These values were in accordance with the findings of Yoo and Lee, 2016, Makori et al 2017and Nyadjeu et al (2018 and could partially justify the absence of mortality observed throughout the study, coupled with experimental fish's apparent good health observed through the results on both the growth and feed utilization.…”
Section: Discussionsupporting
confidence: 90%
“…The average values of water quality parameters such as temperature, transparency, pH, dissolved oxygen, nitrite, nitrate, and ammonia monitored throughout the trials were considered as suitable for the survival, normal growth, as well as good general physiology of O. niloticus. These values were in accordance with the findings of Yoo and Lee, 2016, Makori et al 2017and Nyadjeu et al (2018 and could partially justify the absence of mortality observed throughout the study, coupled with experimental fish's apparent good health observed through the results on both the growth and feed utilization.…”
Section: Discussionsupporting
confidence: 90%
“…Results presented in Table 1 reveals that the pH of water from both ponds are in the alkaline range, although that of the earthen pond is more alkaline (8.6) than that of the plastic pond (7.5). While this pH range is consistent with the quality of water tolerable to many fish species (Makori et al, 2017;Deekae et al, 2010), the value obtained for the earthen pond is slightly above the upper limit of 6.5 -8.5 specified by the world health organization (WHO, 2011). The pH values are in agreement with the alkalinity of the pond waters, a measure of the ability to neutralize strong acids, usually expressed as mg/L CaCO3.…”
Section: Physico-chemical Characteristics Of Water From Earthen and Psupporting
confidence: 78%
“…In addition, the length and mass measurements recorded in this study as well as the growth rate are comparable to those from a previous study on O. mossambicus from a natural environment in which 1-day-old larvae had a mean standard length of 4 mm 39 and O. niloticus Table 1: Mean total length, mass and condition factor of control fish exposed to borehole water (Control) or the solvent dimethysulfoxide (DMSO) and of nevirapine-exposed fish The strong positive correlation between length and mass measurements, and between fish age and both length and mass measurements, in all groups, confirmed that as the larval and juvenile stages of O. mossambicus were aging, they were also increasing both in length and in mass, as is the case for healthy fish. 28,40 If NVP in water had a negative impact on fish growth, the relationship between length and mass would have been affected, and the correlation would not have been strong and positive. In fisheries, healthy fish are characterised by strong positive mass-length, age-length and age-mass relationships; and length measurements are the most used in regressive models to predict either fish age or fish mass.…”
Section: Discussionmentioning
confidence: 99%
“…The fish in all three groups had a high and rapid mean SGR from Day 1 to Day 30; from Day 30 to Day 60, the mean SGR decreased in all groups but was still high compared to the SGR recorded for O. niloticus in their natural environment. 40 O. mossambicus early life stages are known to have a fast and high initial growth rate to allow them to reach large sizes quickly in order to avoid predation. 41 According to Sparre and Venema 29 , in normal conditions, the growth rate of a healthy fish decreases as the fish gets older, becoming zero when the fish gets to its maximal growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation